PENGARUH DIAMETER VARIASI THROTTLE BODY TERHADAP DAYA, TORSI DAN EMISI GAS BUANG PADA SEPEDA MOTOR BEAT PGM-FI 110 CC TAHUN 2014 - Remon Lapisa; Rizky Rahman; Irma Yulia Basri; Wanda Afnison (Ensiklopedia Education Review, 2022)
This study is to find out how the diameter of the throttle body is 22mm, 24mm, and 26mm. Regarding torque, power, and exhaust emissions on the Beat-PGM FI 110 cc motorcycle in 2014. This was done as an effort to improve engine performance. This study uses an experimental approach. Data retrieval directly from motorcycles which measured torque and power using a dynamometer, as well as a gas analyzer aims to test exhaust emissions resulting from testing each type of throttle body. The results of the tests carried out with variations in the diameter of the throttle body 22 mm, 24 mm, and 26 mm showed the best torque results obtained on the 24 mm throttle body, which was 7.765 N.m at 6000 rpm. This means that the torque has increased by 5.8% from the test results using a standard throttle body. The best power results obtained on a 24 mm throttle body is 6.6075 HP at 7,000 rpm. This means that the power has increased by 4.5% from the test results using a standard throttle body. The best emission results obtained on a 24 mm throttle body, namely CO decreased by an average of almost close to 50% as well as HC.Keywords: Throttle Body, Torque and Power, Exhaust Emissions, EFI